LDPE composite films incorporating ceramic powder emitting far‐infrared radiation for advanced food‐packaging applications. Issue 13 (15th December 2015) - Ketsuk, Phuntheera; Lim, Mijin; Baek, Seung Hye; Jung, Jeyoung; Kim, Dowan; Malegowd, Raghavendra Gownolla; Seo, Jongchul; Khan, Sher Bahadar
ABSTRACT: A ceramic powder that emits far‐infrared radiation (FIR) was incorporated into low‐density polyethylene (LDPE) via melt‐compounding and subsequent melt‐extrusion processes. To investigate the feasibility of as‐prepared LDPE/FIR composite films for use in packaging applications, the composite films were characterized using Fourier transform infrared spectroscopy, X‐ray diffraction, scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry, FIR emissivity and emissive power, antimicrobial activity assays, and storage tests. The physical properties and antimicrobial activities of the composite films were found to strongly correlate with the changes in the chemical and morphological structures that originate from different contents of FIR ceramic powder. A higher content of FIR ceramic powder in the LDPE/FIR composite film provided increased FIR emissivity and emission power of the composite and resulted in good antimicrobial activity. Storage tests also showed that incorporation of FIR ceramic powder into LDPE film was an effective method for maintaining the freshness of lettuce. Furthermore, the incorporation of FIR ceramic powder into LDPE films induced higher thermal stability and crystallinity and enhanced their barrier properties, which suggest these LDPE/FIR composite films are potential candidates for advanced packaging materials for the food and medical industries. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43102. Abstract :